Slow or swift, your patients' experience won't drift: absence of correlation between physician productivity and the patient experience. Issue 5 (7th November 2016) - Lenz, Kasia; McRae, Andrew; Wang, Dongmei; Higgins, Benjamin; Innes, Grant; Cook, Timothy; Lang, Eddy
Absract: Objectives: To evaluate the relationship between Emergency Physician (EP) productivity and patient satisfaction with Emergency Department (ED) care. Methods: This retrospective observational study linked administrative and patient experience databases to measure correlations between the patient experience and EP productivity. The study was performed across three Calgary EDs (from June 2010 to July 2013). Patients>16 years old with completed Health Quality Council of Alberta (HQCA) ED Patient Experience Surveys were included. EP productivity was measured at the individual physician level and defined as the average number of patients seen per hour. The association between physician productivity and patient experience scores from six composite domains of the HQCA ED Patient Experience Survey were examined using Pearson correlation coefficients, linear regression modelling, and a path analysis. Results: We correlated 3, 794 patient experience surveys with productivity data for 130 EPs. Very weak non-significant negative correlations existed between productivity and survey composites: "Staff Care and Communication" (r=-0.057, p =0.521), "Discharge Communication" (r=-0.144, p =0.102), and "Respect" (r=-0.027, p =0.760). Very weak, non-significant positive correlations existed between productivity and the composite domains: "Medication Communication" (r=0.003, p =0.974) and "Pain management" (r=0.020, p =0.824). A univariate general linear model yielded no statistically significant correlations between EP productivity and patient experience, and the path analysis failed to show a relationship between the variables. Conclusion: We found no correlation between EP productivity and the patient experience. RÉSUMÉ: Objectif: L'étude visait à évaluer la relation entre la rapidité des médecins d'urgence (MU) et le degré de satisfaction des patients au regard des soins reçus au service des urgences (SU). Méthode: Il s'agit d'une étude rétrospective d'observation dans laquelle des données administratives ont été liées à des données sur l'expérience des patients afin de mesurer le degré de corrélation entre l'expérience des patients et la productivité des MU. L'étude a été menée dans trois SU, à Calgary (juin 2010 – juillet 2013). Ont été inclus dans l'étude des patients>16 ans ayant rempli le questionnaire Health Quality Council of Alberta (HQCA) sur leur expérience au SU. Pour ce qui de la productivité des MU, elle a été mesurée sur une base individuelle et elle a été définie comme le nombre moyen de patients examinés à l'heure. La relation entre la productivité des MU et l'expérience des patients, fondée sur les résultats obtenus dans 6 domaines composés de l'HQCA relativement à l'expérience des patients au SU a été examinée à l'aide de coefficients de corrélation de Pearson, d'un modèle de régression linéaire et d'une analyse des pistes causales. Résultats: Au total, 3794 questionnaires sur l'expérience des patients ont été mis en corrélation avec des données sur la productivité concernant 130 MU. Se sont dégagées des analyses, des corrélations négatives, très faibles, non significatives entre la productivité et les domaines composés liés aux communications et aux soins donnés par le personnel (r=-0, 057; p =0, 521), aux communications au moment du congé (r=-0, 144; p =0, 102) et au respect (r=-0, 027; p =0, 760). Se sont aussi dégagées des analyses, des corrélations positives, très faibles, non significatives entre la productivité et les domaines composés liés aux communications relatives aux médicaments (r=0, 003; p =0, 974) et à la prise en charge de la douleur (r=0, 020; p =0, 824). D'ailleurs, un modèle de régression linéaire général et unidimensionnel a fait ressortir l'absence de corrélation statistiquement significative entre la productivité des MU et l'expérience des patients, et il en est allé de même pour l'analyse des pistes causales au regard des relations entre les différentes variables. Conclusion: L'étude n'a pas permis d'établir de relation entre la productivité des MU et l'expérience des patients.